2012
DOI: 10.2169/internalmedicine.51.6581
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Physical Activity Level and Completion Rate of Small Bowel Examination in Patients Undergoing Capsule Endoscopy

Abstract: Objective Capsule endoscopy (CE) allows direct examination of the small bowel in a safe, noninvasive and well-tolerated manner. Nonetheless, experience indicates failure to reach the cecum in 20-30% of patients within the 8 hour battery life. Attempts to improve the completion rate (CR) as defined by reaching the cecum have been unsuccessful. This study was to investigate the relationship between patients' physical activity and CR. Methods Between January 2009 and January 2010, 76 patients (44 men, 32 women; m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 25 publications
(22 reference statements)
0
16
0
Order By: Relevance
“…Due to this size, we were able to avoid the confounding factor of hospitalization status that limited all previous studies. We were unable to assess the mobility of the hospitalized patients, which may have affected transit times 14 . However, there were only 2 patients in the endoscopically placed group who were in the intensive care unit and there was no mention of strict bed rest orders for the other patients.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this size, we were able to avoid the confounding factor of hospitalization status that limited all previous studies. We were unable to assess the mobility of the hospitalized patients, which may have affected transit times 14 . However, there were only 2 patients in the endoscopically placed group who were in the intensive care unit and there was no mention of strict bed rest orders for the other patients.…”
Section: Discussionmentioning
confidence: 99%
“…There have been minimal data presented on the rate of completed studies and on the diagnostic success of VCE carried out in this setting. Study completion is a particular concern as cardiac monitoring limits patient movement and immobility has been previously linked with incomplete VCE studies . Only two series have reported completion rates and they had divergent results when compared to the average VCE completion rate of 83.5% .…”
Section: Introductionmentioning
confidence: 99%
“…Study completion is a particular concern as cardiac monitoring limits patient movement and immobility has been previously linked with incomplete VCE studies. 11 Only two series have reported completion rates and they had divergent results when compared to the average VCE completion rate of 83.5%. 9,12,13 To our knowledge, only one series of 20 patients describes the diagnostic yield of the procedures.…”
Section: S Ince Its Introduction In 2000 Video Capsulementioning
confidence: 99%
“…Hospitalization has been pointed out as a risk factor for incomplete small bowel examinations [23,24,25]. Shibuya et al [26] suggested that increasing physical activity would increase the likelihood of a complete bowel examination by CE. In contrast, two reports suggest that a prolonged small bowel transit time during CE may be associated with a higher diagnostic yield [27,28].…”
Section: Discussionmentioning
confidence: 99%